1988
DOI: 10.1002/hep.1840080626
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic liver disease: Quantitation of parenchymal and cyst volumes from computed tomography images and clinical correlates of hepatic cysts

Abstract: Polycystic liver disease is a common manifestation of autosomal dominant polycystic kidney disease. However, factors that regulate hepatic cystogenesis have not been defined, and the effect of cyst formation on hepatic parenchymal mass has not been studied. We validated computed tomographic methods for measuring volumes from computed tomographic images using plastic-agar models and demonstrated that measured volumes were within 10% of actual volumes. The validated methods were used to measure hepatic parenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(45 citation statements)
references
References 25 publications
1
43
0
1
Order By: Relevance
“…Computed tomographic methods to measure cystic volume in plastic agar models (in this model plastic cysts were embedded in agar) and in patients with ADPKD (without intravenous injection of contrast) had shown that this method is valid and accurate. 41,42 Our published data 43 also suggest that micro-CT images could be used to precisely measure the total liver tissue volume. In the PCK rat, liver parenchyma and cysts (based on differences in their densities) were easily defined by micro-CT images.…”
Section: Discussionmentioning
confidence: 94%
“…Computed tomographic methods to measure cystic volume in plastic agar models (in this model plastic cysts were embedded in agar) and in patients with ADPKD (without intravenous injection of contrast) had shown that this method is valid and accurate. 41,42 Our published data 43 also suggest that micro-CT images could be used to precisely measure the total liver tissue volume. In the PCK rat, liver parenchyma and cysts (based on differences in their densities) were easily defined by micro-CT images.…”
Section: Discussionmentioning
confidence: 94%
“…Patients with PCLD can be arbitrarily divided into two groups, massive or minimal, based on a definition for mass of total liver cyst/parenchymal volume ratio > 1. 76 Using this definition, most symptomatic cases are restricted to patients with massive hepatic cystic disease with abdominal pain and discomfort and shortness of breath correlating with severity of hepatic cystic disease. l8 Typically, liver parenchymal volume is preserved despite extensive hepatic cystic disease and extraordinary distortion of hepatic architecture (Fig.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The most common extrarenal manifestation, accounting for up to 10% of ADPKD morbidity and mortality, is the development of liver cysts. Within a clinically affected liver the parenchymal volume does not change significantly (7), but the liver can have hundreds of distinct cysts, with cysts reaching several centimeters in diameter. In the liver, the clinical manifestations of ADPKD are associated directly with the compression of the surrounding tissues, organs, and vasculature.…”
mentioning
confidence: 99%